2014
DOI: 10.1007/s11906-014-0483-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Risk Factors for Hypertension: an Update of the Literature

Abstract: A growing body of research demonstrates that psychosocial factors play an important role in the development of hypertension. Previous reviews have identified several key factors (i.e., occupational stress) that contribute to the onset of hypertension, however they are now outdated. In this review, we provide an updated synthesis of the literature from 2010 to April 2014. We identified 21 articles for inclusion in the review, of which there were six categories of psychosocial stressors: occupational stress, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
107
3
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(136 citation statements)
references
References 64 publications
(115 reference statements)
9
107
3
10
Order By: Relevance
“…Like prior reviews [4,5,7,10,26-29,55], research from the last three years suggests that anxiety and depression are associated with a higher risk of hypertension. Although the associations appear to be in expected directions, less firm conclusions can be drawn regarding the specific role of anger and PPWB, with fewer methodologically rigorous studies published recently.…”
Section: Summary Of the Recent Findings In The Context Of Prior Mixedmentioning
confidence: 81%
See 1 more Smart Citation
“…Like prior reviews [4,5,7,10,26-29,55], research from the last three years suggests that anxiety and depression are associated with a higher risk of hypertension. Although the associations appear to be in expected directions, less firm conclusions can be drawn regarding the specific role of anger and PPWB, with fewer methodologically rigorous studies published recently.…”
Section: Summary Of the Recent Findings In The Context Of Prior Mixedmentioning
confidence: 81%
“…Due to space constraints, other relevant psychosocial factors such as discrimination and social support/isolation [2,5,6,9,10] were not considered. Articles were not included if they: 1) tested experimental tasks or psychosocial interventions; 2) considered hypertension as a risk factor for psychological distress; 3) were based on clinical/medical samples; or 4) monitored BP with a 24-hour ambulatory assessment, which does not provide information on hypertension onset specifically.…”
Section: Methodological Approachmentioning
confidence: 99%
“…Stress can influence blood pressure (Busnardo et al, 2013) and may contribute to hypertension (Cuffee et al, 2014). Corticotropin releasing factor (CRF) and its type 1 receptor (CRF 1 ) in the PVN and other brain areas have long been associated with both stress responses and with homeostatic regulation (Goncharuk et al, 2002; Ku et al, 1998; Smith et al, 1998).…”
mentioning
confidence: 99%
“…36,37) Relative to other CVD, such as CAD and CHF, the impact of HT on HR-QOL may be less, but it is reported that psychosocial factors contribute to the development of HT, and a higher level of BP induced more physical, emotional, and psychosocial impairments. 17,38) Since it often takes long-term treatment to manage HT, maintenance of adherence to treatment is critical to avoid treatment dropout. Therefore, physicians must evaluate patients' HR-QOL comprehensively from various points of view and follow them up in clinical settings.…”
Section: Discussionmentioning
confidence: 99%